Cross-cultural maritime technological exchange in the first-millennium Indian Ocean - Vosmer, Tom (Proceedings of the Seminar for Arabian Studies, 2022)
Extensive trade networks in the Indian Ocean generated contact among cultures and spheres of maritime technology across a huge geographical area. Inevitably, these networks resulted not only in exchange of foodstuffs, raw materials, luxury goods, spices, and manufactured goods, but also in cultural and religious concepts and technological knowledge and practices. With the intensity of maritime trade these exchanges engendered the borrowing of shipbuilding designs, materials, and methodologies and generated a certain hybridization of technology, design, and the ways in which ships were conceived. This hybridization is particularly evident in the Belitung and Phanom-Surin ships discovered in Indonesia and Thailand respectively (Flecker 2001; 2008; Jumpron 2019; Wongnai, Jumpron & Premjai 2016). While echoing shipbuilding practices from outside South-East Asia, they also incorporated materials and concepts from South-East Asia, and yet remain distinct from the dominant lashed-lug construction of the region. Using archaeological material from Oman and South-East Asia as well as ethnographic data from the western Indian Ocean, East Africa, India, Oman, Iran, and South-East Asia, this paper explores current archaeological and ethnographic shipbuilding information and raises some questions about the place of Belitung and Phanom-Surin in first-millennium shipbuilding practice.